Matthew B. Roller, Models from the Past in Roman Culture. A world of Exempla, Cambridge, Cambridge University Press, 2018, 321 pp. [ISBN: 978-1-316-61490-7]. - Sánchez González, Víctor (Gerión. Revista de Historia Antigua, 2021)
Reseña de la obra de Matthew B. Roller, Models from the Past in Roman Culture. A world of Exempla, Cambridge, Cambridge University Press, 2018, 321 pp. [ISBN: 978-1-316-61490-7].